The incidence and risk of osteoporosis in patients with anxiety disorder: A Population-based retrospective cohort study - Hong-Jhe, Chen (Medicine (Baltimore), 2016)
The purpose of this study was to investigate the relationship between anxiety disorder (AD) and the subsequent development of osteoporosis. We conducted a population-based retrospective cohort analysis according to the data in the Longitudinal Health Insurance Database 2000 of Taiwan. We included 7098 patients in both the AD and no-anxiety cohort who were matched according to age and sex between January 1, 2000, and December 31, 2013. The incidence rate and the risk ratios (RRs) of subsequent new-onset osteoporosis were calculated for both cohorts. We used Cox proportional hazards models to assess the effect of AD. The Kaplan–Meier method was applied to estimate the cumulative osteoporosis incidence curves. The AD cohort consisted of 7098 patients, and the comparison cohort comprised the same matched control patients without anxiety. The risk of osteoporosis was higher in the AD cohort than in the comparison cohort. In addition, the incidence of newly diagnosed osteoporosis remained significantly increased in all of the stratified follow-up durations (0–1, 1–5, 5–10, ≥10years). Patients with AD were 1.79 times more likely to get osteoporosis than those without AD. We also observed a significant increase in osteoporotic risk in AD patients who are comorbid with hypertension, diabetes mellitus, and chronic liver disease. The incidence of osteoporosis in Taiwan is associated with an a priori AD history. The risk ratios are the highest for osteoporosis within 1 year of AD diagnosis, but the risk remains statistically significant for >1 year. Clinicians should pay particular attention to osteoporotic comorbidities in AD patients.